MANAJEMEN PRODUK EKONOMI KREATIF OLAHAN SINGKONG TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA PANCUR BATU - Juliana Simbolon; Darnianti Darnianti; Daniel Maruli Tua Gultom; Marselius Butarbutar; Roy Sipayung (Universitas Quality, 2023)
The creative economy is a form of human activity related to creativity and innovation in the development of a product. In order for the products produced to develop properly, a management is needed. Management is needed to organize and coordinate the factors of production to increase the value and benefits of a product or service that is produced efficiently, through the use of knowledge and skills. The product management system used in the development of the creamy cassava business in Pancur Batu Village, North Sumatra, is by providing new innovations to the products it produces in terms of variants and shapes. With this new innovation, processed cassava products can continue to survive in the market until now. The purpose of this study was to determine the management of creative economy products processed by cassava on people's welfare. This type of research was field research or often known as field research. The nature of the research used was descriptive qualitative and in this study used an inductive way of thinking using primary and secondary data sources. The goal was to be able to describe the Management of Creative Economy Products on Community Welfare. Data collection techniques used were interviews, observation and documentation. Based on the results of the study it could be concluded that the existence of a creamy cassava business in Pancur Batu Village, North Sumatra, had a positive impact. Because for the people of Pancur Batu apart from creating prosperity by reducing the number of unemployed, this business could also increase family income and the income of the surrounding community.